MANAJEMEN PROGRAM GERAKAN LITERASI SEKOLAH DALAM MENUMBUHKAN MINAT BACA SISWA SD DI GUGUS 1 INDRAPURI ACEH BESAR - Sardani Sardani; Khairuddin Khairuddin; Nasir Usman (Jurnal Visipena, 2021)
The management of the School Literacy Movement is a process of planning, organizing, motivating, supervising, evaluating, and empowering all of the school resources to reach the goal of the literacy movement program effectively and efficiently. The aims of this research were to find out: (1) the planning of the school literacy movement program; (2) the implementation of the school literacy movement program; (3) the evaluation of the implementation of the school literacy movement program. This research used a qualitative approach and a descriptive method. The subjects of this research were the school principal, school committee, teachers, the head of the school library, and students in Cluster I of Elementary School Indrapuri of Aceh Besar Regency. The data were collected by using observation, interview, and documentation study. The data were analyzed by using a data reduction technique, data display, and followed by a conclusion. The results showed that: (1) the planning of school literacy movement program at each school in Cluster I of Elementary School Indrapuri had to formulate the stages of habituation, development, and learning based on school strategical plan and reference from Ministry of Education and Culture in 2015 to promote the students’ reading interest; (2) the implementation of a school literacy program in Cluster I of Elementary School Indrapuri to increase the reading interest was done by implementing 15 minutes reading of a supplementary book which is available at the reading corner. Some schools still faced the problem of lack of supplies of reading books in schools; (3) The result of the evaluation of the school literacy program in Cluster I of Elementary School Indrapuri showed the increase of students’ reading interest with the intensity of reading at the reading corner and library. The main challenge faced by the school was the students who still struggled to write the resume and self-made project. Abstrak Gerakan Literasi Sekolah yang dirangcang untuk menumbuhkan minat baca siswa melalui ekosistem literasi sekolah agar meningkatkan kemampuan berpikir, mengakses, mengolah informasi serta menyampaikan kembali informasi. Penelitian ini bertujuan mendeskripsikan: (1) perencanaan program gerakan literasi; (2) implementasi gerakan literasi sekolah; (3) mengevaluasi implementasi gerakan literasi sekolah. Penelitian ini menggunakan pendekatan kualitatif dan metode deskriptif. Subjek penelitian ini terdiri dari kepala sekolah, komite sekolah, guru, kepala pustaka dan siswa di SD gugus 1 Indrapuri Aceh Besar. Teknik pengumpulan data dengan observasi, wawancara dan studi dokumentasi. Adapun teknik analisis data yaitu reduksi data, display data dan menarik kesimpulan. Adapun hasil penelitian ini yaitu: (1) Perencanaan program gerakan literasi sekolah sudah disusun dengan baik dan mempertimbangkan ketentuan yang di keluarkan oleh Kemendikbud Tahun 2015 untuk menumbuhkan minat baca siswa; (2) Implementasi program gerakan literasi sekolah di SD gugus 1 Indrapuri sudah sesuai dengan standar program litarasi, dan mengalami kendala pada keterbatasan bahan bacaan di sekolah; (3) Hasil evaluasi kegiatan program gerakan literasi sekolah di SD gugus 1 Indrapuri Aceh Besar sebahagian besar siswa sudah terlihat peningkatan minat siswa untuk membaca, meskipun masih ada sebahagian siswa yang belum mampu membuat resume dan membuat karya sendiri. Kata Kunci: Gerakan Literasi Sekolah, Minat Baca